Feeding Management, Mineral Status and Blood Biochemical Profile of Dairy Cattle in Mizoram - Malsawmthangi, Suzanne; Samanta, Arup Kumar (Indian Journal of Animal Nutrition, 2017)
The present study was conducted to assess the feeding management, mineral status and blood biochemical profile of dairy cattle in Mizoram. A total of 104 dairy farmers from 52 villages of all eight districts of Mizoram viz., Aizawl, Lunglei, Lawngtlai, Kolasib, Serchhip, Mamit, Saiha and Champhai were selected and blood samples (n=260) were collected from dairy cattle and analysed for minerals and other biochemical parameters. The average serum concentration of Ca, Mg and P was 7.27, 1.96 and 3.22 mg/dL, respectively was found to be below the critical limits. The average mean values for Cu, Fe, Zn, Mn and Co in blood serum were 0.58, 1.02, 0.58, 0.19 and 0.002 ppm, respectively and the concentration of all the micro minerals in serum except that of Fe was below the critical value. The average levels of blood glucose, serum total protein, albumin, globulin, urea and creatinine were found to be 44.82 mg/dL 6.86 g/dL, 3.04 g/dL, 3.82 g/dL, 43.82 mg/ dL and 1.38 mg/dL, respectively. It could be concluded that most of the dairy cattle were deficient in most of the minerals and there is an urgent need of supplementation of required minerals for optimum production and overall health of the animals.